The OPEC Fund for International Development : the formative years - Shihata, Ibrahim F. I. (London : Croom Helm ; New York : St. Martin's Press, 1983)
This book examines the OPEC organizational evolution into a fully-fledged international body. The Fund's achievements in providing loans and grants to over 80 countries were also described.
Includes index
Includes bibliographical references.
usc12/06/18
Loans
Keywords: Economic assistance